STRATEGI PENGEMBANGAN AGROINDUSTRI KERIPIK JAHE (JAHEKU) DI DESA KOTA RAYA KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Evy Maharani; Novi Dwi Ningsih; Shorea Khaswarina (DINAMIKA PERTANIAN, 2017)
Agroindustry as the development of agricultural sector expected can play a part in to create a market to agriculture pickings through various its product of him. The strategy is big scale plan which has future reach priority which far is and also specified in such a manner so that enable organization to have interaction to effectively with its environment in a condition aimed at all emulation optimization attainment of target with a various pertinent organizational target. This research revenue analysis aim to the effort my ginger and compile correct development strategy to a worker of ginger in Kota Raya Village Rengat District Indragiri Hulu Regency. Result of research of Amount produce its month; moon ginger flaky that is 360 bale, whereas in acceptance to the effort my ginger that is Rp. 5.400.000. obtained net earning the effort my ginger Rp. 2.764.000 per month. correct Development strategy to worker of ginger flaky is: Increase product ginger flaky to fulfill request of market, conducting ginger flaky promotion and make more interesting tidiness to be an access to market broader, Maintaining market which has there is and looks for new market by improving opportunity of promotion by following existing exhibition; Braid cooperation with relevant institute to be is tough of capital employed and self-service to market product, managing health permit so that marketing of broader ginger flaky; Take care of the availability of raw material at the time of price of fluctuating and do product continuity by providing raw material stock and avoid too kept old raw material; Improve standard quality of especial raw material, supporter raw material in order not to easy to destroy, and also look for market information through newspaper, on duty commerce and follow existing exhibition, making better product can fulfill request of market.